Revealing the regulation of learning strategies of MOOC retakers: A learning analytic study. (March 2022) - Fan, Yizhou; Jovanović, Jelena; Saint, John; Jiang, Yuhang; Wang, Qiong; Gašević, Dragan
Abstract: Massive Open Online Courses (MOOCs) have already shown a great potential to be used as an alternative model for teacher professional development (TPD). Not only do MOOCs offer relevant content and activities, but they also provide opportunities for strengthening the skills for self-regulated learning of teachers as life-long learners. In this study, we focused on a unique sub-group of MOOC learners – retakers who take the same TPD MOOC multiple times. In the empirical study reported in this paper, we examined what learning strategies they choose when taking a TPD MOOC and the extent to which they are able to adapt their learning strategies to improve their performance in the subsequent attempts. By using learning analytic methods, we detected five learning strategies and eight major forms of strategy change adapted by MOOC retakers. We found that two strategy changes (from Content-Oriented Strategy to Intensive-Thorough Strategy or Balanced Strategy ) with associated with significantly higher performance in the subsequent attempts compared to no change in strategy. Our findings have implications for MOOC instructors and providers about the ways they can support MOOC retakers. Our findings also suggest that MOOCs are not only valuable TPD resources for teachers, but they also have unique opportunities for strengthening the self-regulation skills of teacher learners as the "by-products of learning". Highlights: We focused on a unique sub-population of MOOC learners -- retakers who take the same MOOC multiple times. We examined what learning strategies retakers choose when taking a teacher professional development MOOC. We also examined the extent to which they were able to adapt their learning strategies to improve their performance. We find that MOOCs are valuable as both professional development resources and opportunities for strengthening SRL skills.